INFLUENCIA DEL TAMAÑO DE PARTÍCULA Y pH EN LA BIOADSORCIÓN DE CROMO EN EFLUENTES DE CURTIEMBRE CON CÁSCARA DE Passiflora edulis – MARACUYÁ. - Jiménez Burgos, Jhonatan Augusto (2022)
ABSTRACT The effect produced by the pH and particle size in the bioadsorption process of a solution with chromium III was determined, using Passiflora edulis and sand, in a fixed-bed column made manually, evaluating the percentage of removal. Regarding the process, Passiflora edulis mixed with sand was conditioned in the glass column, in order to prevent it from compacting when the solution is poured; the solution with chrome was used at pH: 1.37, 2.37 and 3.37; the particle sizes of the bioadsorbent to be used were mesh No. 200 and No. 230 according to the U.S. system. standard; the solution extracted from the tannery was diluted so that it can be analyzed by atomic absorption spectrophotometry. The results analyzed in the laboratory were: 27.16 ppm of concentration and 50.73% of final optimal yield reached in test 4, at pH 2.37 and at mesh No. 200 (particle size).